Parenting styles are associated with overall child dietary quality within low-income and food-insecure households. Issue 15 (17th June 2019) - Burke, Michael P; Jones, Sonya J; Frongillo, Edward A; Blake, Christine E; Fram, Maryah S
Abstract: Objective: To examine the association between parenting styles and overall child dietary quality within households that are low-income and food-insecure. Design: Child dietary intake was measured via a 24 h dietary recall. Dietary quality was assessed using the Healthy Eating Index-2005 (HEI-2005). Parenting styles were measured and scored using the Parenting Styles and Dimensions Questionnaire. Linear regressions were used to test main and interaction associations between HEI-2005 scores and parenting styles. Setting: Non-probability sample of low-income and food-insecure households in South Carolina, USA. Participants: Parent–child dyads ( n 171). Parents were ≥18 years old and children were 9–15 years old. Results: We found a significant interaction between authoritative and authoritarian parenting style scores. For those with a mean authoritarian score, each unit increase in authoritative score was associated with a higher HEI-2005 score ( b = 3·36, P < 0.05). For those with an authoritarian score that was 1sd above the mean authoritarian score, each unit increase in authoritative score was associated with a higher HEI-2005 score ( b = 8.42, P < 0.01). For those with an authoritarian score that was −1sd below the mean authoritarian score, each unit increase in authoritative score was associated with a lower HEI-2005 score; however, this was not significant ( b = −1·69, P > 0·05). Permissive parenting style scores were negatively associated with child dietary quality ( b = −2·79, P < 0·05). Conclusions: Parenting styles should be considered an important variable that is associated with overall dietary quality in children living within low-income and food-insecure households.